Exploring factors relevant in the assessment of the return-to-work process of employees on long-term sickness absence due to a depressive disorder: a focus group study - Muijzer Anna; Brouwer Sandra; Geertzen Jan H; Groothoff Johan W (BMC, 2012)
Abstract Background Efforts undertaken during the Return-to-Work (RTW) process need to be sufficient in order to optimize the quality of the RTW process. The purpose of this study was to explore factors relevant to Return-to-Work Effort Sufficiency (RTW-ES) in cases of sick-listed employees with a Depressive Disorder (DD). Method A case of a long-term sick-listed employee with a DD applying for disability benefits was used to gather arguments and grounds relevant to the assessment of RTW-ES. Two focus group meetings were held, consisting of Labor Experts working at the Dutch Social Insurance Institute. Factors were collected and categorized using the International Classification of Functioning, Disability and Health (ICF model). Results Sixteen factors relevant to RTW-ES assessment in a case of DD were found, categorized in the ICF-model under activities (e.g. functional capacity), personal (e.g. competencies, attitude) and environmental domain (e.g. employer-employee relationship), or categorized under interventions, job accommodations and measures. Conclusions This study shows that 16 factors are relevant in the assessment of RTW-ES in employees sick-listed due to DD. Further research is necessary to expand this knowledge to other health conditions, and to investigate the impact of these results on the quality of the RTW-ES assessment.